Native Language Interference in the spoken target - Porras Cisternas, Cristina Isabel (2010)
Resumen: In this research we will deal with the problem of native language interference in the spoken target language. A case study of three speakers of English as a foreign language. The population chosen for this research was English volunteer teachers with a good level and fluent spoken English. The investigation consists on a recorded interview and two conferences directed by the teachers to students. These conferences took place in "Los Alamos" school and were given to high school students. After making the respective transcriptions the conferences were analyzed to find all the errors corresponding native language interference, and these were classified into charts according to the variables grammar structure and Lexicon, considering several indicators on each case. In the period of around six months of study I found that the highest frequency or errors occur in the variable, Grammar Structures with the indicator subject Pronouns, the rate is followed by the use of prepositions. In the variable Lexicon we can appreciate a higher rate of recurrence in the invention of vocabulary. It is very important to con sider that these a re not global statistics just the result of the study in this particular population although the collected information can be helpful for further studies in the foreign language speakers residents.